2010
DOI: 10.3390/medicina46050043
|View full text |Cite
|
Sign up to set email alerts
|

The value of clinical prognostic factors for survival in patients with invasive urinary bladder cancer

Abstract: The aim of the study was to evaluate the value of clinical prognostic factors for survival of patients with invasive urinary bladder cancer treated with radical cystectomy, chemotherapy, and radiotherapy. Material and methods. A total of 115 patients with invasive urinary bladder cancer were analyzed. Twenty-three patients with invasive urinary bladder cancer (pT2–T4) were treated according to the protocol of a prospective clinical study. In all the cases, transurethral resection was followed by radiation and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 17 publications
(18 reference statements)
0
14
0
Order By: Relevance
“…A similar opinion was suggested by another study in which a reduced chemoradiotherapy dose was found to be a significant predictor of reduced survival in patients with MIBC. 8 Urinary disorders were more characteristic of the IAC þ R group than of the other groups. Given the fact that the frequency of this symptom was remarkably higher in the IAC þ R group than in the IAC group, the addition of radiotherapy to IAC is thought to be associated partly with the occurrence of these urological symptoms.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…A similar opinion was suggested by another study in which a reduced chemoradiotherapy dose was found to be a significant predictor of reduced survival in patients with MIBC. 8 Urinary disorders were more characteristic of the IAC þ R group than of the other groups. Given the fact that the frequency of this symptom was remarkably higher in the IAC þ R group than in the IAC group, the addition of radiotherapy to IAC is thought to be associated partly with the occurrence of these urological symptoms.…”
Section: Discussionmentioning
confidence: 96%
“…6,14,15 Moreover, non-CDDP-based regimens have often been used for SC. 8,16,17 In addition to SC, the intraarterial administration of chemotherapeutic agents 6,14,18 or both systemic and intra-arterial administration 21 have also been reported. Regarding the radiotherapy irradiation range, several patterns have been reported, including the bladder only, 18 bladder plus surrounding tissues, 10,16 and bladder plus pelvis 7,12,14,17,19 The irradiation intensity also varies widely, with total doses to the pelvis of <40 Gy, 17,18 54e60 Gy, 8 >60 Gy, 7,9,12e16 and 40 Gy and an additional 10e20 Gy to the bladder in cases with massive tumours.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The radiotherapy with conventional fractionated dose did not provide benefits to patients with a functioning bladder after transurethral resection. Asadauskiene treated invasive bladder cancer with conventional fractionated radiation scheme . The 3‐year overall survival was 51.1% in the cystectomy group, and only 38.0% in the chemoradiation group ( P = 0.001).…”
Section: Introductionmentioning
confidence: 99%